Iḥyā’ al-Mawāt dalam Kerangka Hukum Pertanahan di Indonesia - Ahmad Munif (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2018)
This paper gives a new conception of iḥyā’ al-mawāt. Iḥyā’ al-mawāt is an effort to revive, manage, and cultivate the land that has not been touched by human before, or has been managed but abandoned in a long time. Islam recommends that humans prosper the land (earth) mandated by God. In the classical fiqh study, iḥyā’ al-mawāt has implications for the acquisition of property rights on the land which is sought iḥyā’ al-mawāt and applies to all types of land. The fact is different from the provisions in the land law that applies in Indonesia. In Indonesia, every inch of land that is not in the name of private and customary rights, the land is a state land. So there is no land without a name. Although there are several types of state land that can be attempted to be managed by government permission. By doing descriptive analysis and comparison to the concept of iḥyā’ al-mawāt and land law in Indonesia, obtained two main conclusions. First, the land of al-mawāt in the framework of land law in Indonesia includes abandoned land, arising land, and reclaimed land. Against these three types of land, may be made iḥyā’ al-mawāt effort by permission of the government. Second, the implications of iḥyā’ al-mawāt in the framework of land law in Indonesia only on the right of utilization and management (ḥaq al-intifā'), not to the acquisition of ownership (al-tamlīk).[]Tulisan ini memberikan konsepsi baru atas iḥyā’ al-mawāt. Iḥyā’ al-mawāt merupakan upaya menghidupkan, mengelola, dan mengolah tanah yang tidak terjamah oleh manusia sebelumnya, atau pernah dikelola namun ditelantarkan dalam kurun waktu yang lama. Islam menganjurkan agar manusia memakmurkan tanah (bumi) yang diamanahkan oleh Tuhan. Dalam kajian fiqh klasik, iḥyā’ al-mawāt berimplikasi kepada pemerolehan hak milik atas tanah yang diupayakan iḥyā’ al-mawāt dan berlaku bagi segala jenis tanah. Kenyataan tersebut berbeda dengan ketentuan dalam hukum pertanahan yang berlaku di Indonesia. Di Indonesia, tiap jengkal tanah yang bukan atas nama pribadi dan hak ulayat, tanah tersebut merupakan tanah negara. Sehingga tidak ada tanah yang tanpa atas nama. Meskipun terdapat beberapa jenis tanah negara yang boleh dikelola atas seijin pemerintah. Dengan analisis deskriptif dan perbandingan terhadap konsep iḥyā’ al-mawāt dan hukum pertanahan di Indonesia, diperoleh dua kesimpulan utama. Pertama, tanah al-mawāt dalam kerangka hukum pertanahan di Indonesia meliputi tanah terlantar, tanah timbul, dan tanah reklamasi. Terhadap ketiga jenis tanah tersebut, boleh dilakukan upaya iḥyā’ al-mawāt atas seizin pemerintah. Kedua, implikasi iḥyā’ al-mawāt dalam kerangka hukum pertanahan di Indonesia hanya pada hak pemanfaatan dan pengelolaan (ḥaq al-intifā'), tidak sampai kepada pemerolehan kepemilikan (al-tamlīk).